Wireless connectivity for health and sports monitoring: a review - Armstrong, S. (British Journal of Sports Medicine, 2007)
This is a review of health and sports monitoring research that uses or could benefit from wireless connectivity. New, enabling wireless connectivity standards are evaluated for their suitability, and an assessment of current exploitation of these technologies is summarised. An example of the application is given, highlighting the capabilities of a network of wireless sensors. Issues of timing and power consumption in a battery-powered system are addressed to highlight the benefits networking can provide, and a suggestion of how monitoring different biometric signals might allow one to gain additional information about an athlete or patient is made. Medicine and sports science can be considered as two linked but contrasting fields of research. Medicine is the science of diagnosing or monitoring the body for ailments that cause the patient to function in a manner that he or she or the doctor considers substandard, and to attempt to return the body to normality. Sports science strives to train and push the body to the extremes of its ability. The two disciplines are more closely linked in research that considers sports injury. Both therefore require a close study of the functions of the body, whether by means of vital signs such as heartbeat and breathing, or by the movement and function of muscles and joints. Often they combine individual variables to determine further information that no one variable can provide.